Tantangan dan Inovasi Pendidikan Karakter Pada Sekolah Dasar Islam Terpadu selama Pandemi Covid-19 di Kota Bandar Lampung - Sunarto; Ruswanto; Umi Kalsum (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The Covid-19 pandemic has profoundly affected numerous aspects of life, notably the educational landscape. The closure of schools and the transition to remote learning pose significant hurdles in fostering character education within Integrated Islamic Primary Schools (SDIT). This research delves into the obstacles and innovative approaches undertaken in character education at SDIT Permata Bunda and SDIT Pelita Khoitul Ummah in Bandarlampung City amid the Covid-19 pandemic. Employing a qualitative methodology with a case study approach, the study involved comprehensive interviews with educators, students, and parents, coupled with an analysis of school program documentation. Findings reveal that adapting to digital technology emerges as a major obstacle, particularly in maintaining vital social interactions essential for character development. Teachers and students are compelled to adopt more interactive and project-based learning methodologies to surmount the challenges posed by remote learning. Furthermore, parental engagement plays a pivotal role in reinforcing character learning at home. Innovations such as project-based online classes, virtual group discussions, and regular principal-parent meetings have augmented the participation and involvement of all stakeholders in the educational process. Despite the adversities encountered, the pandemic has spurred opportunities to devise more creative and efficacious learning strategies. In conclusion, while the Covid-19 pandemic presents multifaceted challenges, embracing innovative learning methodologies and fostering collaboration among stakeholders can substantially bolster the advancement of character education in SDITs. The success of character education hinges not solely on knowledge dissemination but also on collaborative endeavors among schools, students, and parents in fostering a conducive learning environment conducive to nurturing positive values.